Terminator salvation [videorecording (Blu-Ray)] - McG (Joseph McGinty Nichol); Bale, Christian, 1974-; Worthington, Sam, 1976-; Bloodgood, Moon (Warner Bros. Entertainment, 2015)
To save humanity from Skynet and certain extinction, John Connor must rescue a young version of his father and join forces with a former death row inmate from the past.